Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Plenary 2017
DOI: 10.1136/archdischild-2017-313087.4
|View full text |Cite
|
Sign up to set email alerts
|

P04 Developing an early intervention programme for children at high-risk of neurodevelopmental impairment in uganda

Abstract: AimAn estimated 8.4 million newborns annually experience perinatal complications, with possible life-long consequences for their health, development and life chances. This study aimed to develop and evaluate a facilitated, participatory early intervention (EI) programme for infants at high-risk of neurodisability and examine its feasibility, acceptability and impact on child and family quality of life (QoL).MethodsA 10-modular EI programme was developed, adapted from an established programme for older children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The Family Support Programme is based on the existing structure of GTKCP 23 and the EIP 24 , as no other relevant interventions for this target group were identified. Findings from the needs assessment, described above, were used to adapt the programme to meet the specified and identified needs of caregivers of children with CZS in Brazil and gaps in services (May–July, 2017).…”
Section: Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…The Family Support Programme is based on the existing structure of GTKCP 23 and the EIP 24 , as no other relevant interventions for this target group were identified. Findings from the needs assessment, described above, were used to adapt the programme to meet the specified and identified needs of caregivers of children with CZS in Brazil and gaps in services (May–July, 2017).…”
Section: Protocolmentioning
confidence: 99%
“…In Ghana, an evaluation showed that the programme was positively received by families and had a positive impact on both quality of life and knowledge and confidence of caregivers of children with CP, as well as the reported physical and emotional health of the child 23 . The programme was originally designed for children of age 2 and over, and a recent adaptation has been piloted in Uganda for children under 2, the Early Intervention Programme (EIP), and is currently being clinically trialled 24 .…”
Section: Introductionmentioning
confidence: 99%
“…15,16 GTKCP focuses on parents of children aged 2 years and older; a new version, the Early Intervention Program (EIP), was developed for parents of children aged younger than 2 years. 17 Program material is available from www.ubuntu-hub.org.…”
mentioning
confidence: 99%
“…By targeting the caregivers, the programme aims to have an impact on the long-term health, wellbeing, and participation of children with cerebral palsy. An Early Intervention Programme (EIP) has also been developed from GTKCP to address the needs of younger infants [17]. Considering the commonalities of CZS and CP, it may be plausible to use existing CP programmes as the basis for new interventions.…”
Section: Introductionmentioning
confidence: 99%